The Role of Giving Eat Reminder Application Media to Changes in Knowledge, Attitude, Behavior, and Eat Pattern of Adolescent Age 13-15 Years Old - Khaerani, Annisa; Sitoayu, Laras; Melani, Vitria; Gifari, Nazhif; Nuzrina, Rachmanida (JHE (Journal of Health Education), 2020)
Background: Adolescence is a period of transition physical, mental, and emotional changes. Adolescents usually experience lifestyle changes and eating habits such as excessive dieting, skipping meals, using supplements and adopting diets. Methods: The study used the quasy experimental method with pre-test and post-test in the intervention and control groups. The number of samples used in this study amounted to 84 samples. Results: Most of the respondents were male (61.9%) with an average age of 14 years. Based on the analysis carried out showed that there were no significant changes in the knowledge, attitudes, behaviors and eating patterns of adolescents before and after the intervention (p> 0.05), but there was a change in diet, the mean score on knowledge and behavior scores increased. Conclusions: Nutrition education with the application of Remind me application can increase the knowledge, attitudes, behavior and diet of adolescent balanced nutrition, if adolescents are exposed to the media intensely and continuously. Providing the Remind me application media as a media for nutritional education to adolescents still needs to be developed in an effort to perfect the application display, content, specifications of mobile phones or smart phones, better programming system specifications and safer domain server usage will reduce debugging on the application system, so that the message delivered and can be achieved.